Adequacy of Essential Amino Acids for Vegetarian Children in “The Dayak Hindu Budha Bumi Segandhu Tribe Community” in Indramayu - Alvina Fadila Maulida; Ai Nurhayati; Rita Patriasih (Media Pendidikan Gizi dan Kuliner, 2021)
Vegetarian children in the fulfillment of animal protein intake are generally included in the low category. Animal protein is a good source of essential amino acids. The purpose of this study was to obtain information regarding the level of adequacy of essential amino acids for vegetarian children. The method with quantitative descriptive analysis, the sample used by the census technique was taken from all vegetarian children in the research location totaling 8 respondents. The results showed that the limiting amino acid lysine was taken from rice as a staple food and bakwan as a snack. The limiting amino acid tryptophan is extracted from eggs as animal protein. The limiting amino acids methionine and cystine are taken from tofu and tempeh as vegetable protein, mushrooms as vegetables, and bananas as fruit. The level of protein adequacy of respondents was 72.63% in the moderate deficit category. The level of adequacy of the amino acid lysine as a limiter was 84.16% in the mild deficit category, tryptophan 96.56% in the sufficient category, threonine 120% in the sufficient category, methionine and cystine in the excess category 129.13%. Researchers recommend respondents to increase their consumption of foods high in the amino acid lysine, for example eggs according to the Nutritional Adequacy Rate.